2020
DOI: 10.1097/mph.0000000000001958
|View full text |Cite
|
Sign up to set email alerts
|

Novel CUBN Mutation in a Young Child With Megaloblastic Anemia

Abstract: Inherited disorders of cobalamin (Cbl, vitamin B12) metabolism are rare causes of megaloblastic anemia and neurologic abnormalities. More prevalent in certain ethnic groups, these disorders occur despite adequate Cbl intake and usually result from abnormal vitamin cell transport or processing. Cubilin (CUBN, intrinsic factor-cobalamin receptor) is the intestinal receptor for the endocytosis of intrinsic factor—vitamin B12. Its gene is localized to chromosome 10p13 and mutations involving CUBN have been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Schematic of CUBN gene and exons, adapted from Domingo‐Gallego et al 2 Previously reported variants in exons 1–28 previously have been associated with IGS with megaloblastic anemia 2 . Variants in exons 29–67, the region encompassing c.5913_5916del (p.Thr1972Leufs*10) and c.5069C > T (p.Ala1690Val) which were reported here, have been associated with chronic benign proteinuria 2,8–12 …”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…Schematic of CUBN gene and exons, adapted from Domingo‐Gallego et al 2 Previously reported variants in exons 1–28 previously have been associated with IGS with megaloblastic anemia 2 . Variants in exons 29–67, the region encompassing c.5913_5916del (p.Thr1972Leufs*10) and c.5069C > T (p.Ala1690Val) which were reported here, have been associated with chronic benign proteinuria 2,8–12 …”
Section: Introductionsupporting
confidence: 51%
“…Few cases of benign isolated subnephrotic proteinuria in association with C‐terminal cubilin defects have been described in the literature. The spectrum of clinical presentations associated with CUBN pathogenic variants ranges from megaloblastic anemia type 1 (IGS) to isolated benign proteinuria 2,7–10 . The phenotype appears to be dependent on the site of the pathogenic variant within the CUBN gene and the loss of function of certain domains 2,10–12 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations